CORN GLUTEN HYDROLYSIS BY ALCALASE: KINETICS OF HYDROLYSIS - Apar, Dilek Kilic; Ozbek, Belma (TAYLOR & FRANCIS INC, 2010)
In the present study, the reaction kinetics of corn gluten hydrolysis by Alcalase, a bacterial protease produced by Bacillus licheniformis, was investigated. The reactions were carried out for 10min in 0.1L of aqueous solutions containing 10, 20, 30, 40, and 50g protein L-1 corn gluten at various temperature and pH values. The amount of enzyme added to the reaction solution was 0.25% (v/v). Also, to determine decay and product inhibition effects for Alcalase, a series of inhibition experiments were conducted with the addition of various amounts of hydrolysate. For each experimental run, both the amount of hydrolysis (meqvL-1) and the soluble protein amount (gL-1) were investigated with respect to time, and the initial reaction rates were determined from the slopes of the linear models that fitted to these experimental data. The kinetic parameters, Km and Vmax were estimated as 53.77gL-1 and 5.94meqvL-1min-1. The type of inhibition for Alcalase was determined as uncompetitive, and the inhibition constant, Ki, was estimated as 44.68% (hydrolysate/substrate mixture).
Keywords: Alcalase; Corn gluten; Hydrolysis kinetics; Product inhibition; ENZYMATIC-HYDROLYSIS; FUNCTIONAL-PROPERTIES; PROTEINS; SOLUBILIZATION; MEAL; Engineering